Nghiên cứu ảnh hưởng của xử lý plasma đến độ bám dính của lớp phủ khâu mạch quang trên nền polypropylen. Phần 1. Nghiên cứu ảnh hưởng của xử lý plasma không khí đến tính chất bề mặt polypropylen - Phúc, Mạc Văn; Hiệp, Nguyễn Anh; Hùng, Đào Phi; Vương, Nguyễn Thiên; Hiền, Lê Xuân; Thành, Trịnh Văn; Thành, Đỗ Minh (Vietnam Journal of Chemistry, 2015)
In this work, polypropylene (PP) was treated by air plasma to improve its adhesion properties. The inﬂuence of plasma treatment time was studied. As can be showed from results of static contact angle, the air plasma treatment improved significantly hydrophilic property of PP surface - the contact angle was reduced from 109 to 56o, respectively, before and after 3 minutes plasma treatment. In addition, Scanning Electron Microscope (SEM) images showed that after plasma treatment, the morphology of polymer surface saw rougher than before. The results of Fourier Transformed Infrared Spectroscopy (FT-IR) also presented that newly created hydrophilic functional groups (C=O, O-H) on the polypropylene surface caused by plasma treatment. As a result, the lap-shear strengths of PP after plasma treatment were substantially improved. As can be conclude from the results of this study, the suitable plasma treatment time for PP was 3 minutes.